Cognitive-behavioral group therapy for ADHD predominantly inattentive presentation: A feasibility study of a new treatment protocol. Issue 4 (1st December 2022) - Strålin, Elinor Eskilsson; Thorell, Lisa B.; Szybek, Katharina; Lundgren, Tobias; Bölte, Sven; Bohman, Benjamin
Abstract: Attention-deficit/hyperactivity disorder (ADHD) is a highly impairing condition with varying clinical presentations. Psychological treatments for ADHD are often similar, irrespective of predominant symptomatology. However, because inattention and hyperactivity/impulsivity are associated with different challenges in daily life more presentation-specific treatments are warranted. The purpose of the present study was to evaluate the feasibility and explore the preliminary effects of a novel group-based cognitive-behavioral therapy (CBT) protocol for ADHD predominantly inattentive presentation (ADHD-I), with the aim to reduce symptoms of inattention and associated problems. Materials and Methods . Using an open trial design, 39 adult patients with ADHD-I were included. Participants underwent 14 sessions of the new CBT for ADHD-I (CADDI) protocol, which includes skills training in organizing and initiating activity and coping with procrastination and passivity. In addition, mindfulness meditation is practiced throughout treatment. Results . The CADDI protocol proved feasible in terms of session completion and treatment acceptability. However, home assignment completion was moderate and attrition was high. Inattentive symptoms, assessed by clinicians and self-report, were reduced of a medium effect size, (Cohen's d = 0.65 and d = 0.55, respectively) and symptoms of depression of a small effect size ( d = 0.48). An increase of a large effect size was observed for mindfulness meditation ( d = 0.91). No effects were seen in functional impairment, nor in quality of life. Conclusions . The CADDI protocol is a potentially valuable new psychological treatment for adults with ADHD-I, although treatment effects need to be further evaluated and participant retention secured in randomized controlled trials.